Práticas sócioambientais em uma instituição de ensino superior estadual do Paraná - Camargo, Lilian Sanches (2017)
The emergence of the concept of sustainable development has brought about changes in the way companies act in order to adopt everyday practices that show respect and concern for nature. In this context of changes, Higher Education Institutions are also included as they play a fundamental role in the process of changing society, regarding sustainability issues. This study aims to make a diagnosis of socio-environmental practices adopted in a State Higher Education Institution, from the perspective of the Environmental Agenda in Public Administration (A3P). Regarding the approach of the problem, this research is classified as qualitative and for methodological procedures, the case study is used. It was evidenced in the study that there is no environmental policy formally inserted in its management and also that the institution partially complies with the guidelines proposed by the A3P and that the existing actions occur in an isolated. It should be emphasized that the analysis of the results indicated the need to create an environmental agenda on the institution, the creation of a committee to discuss the socio-environmental theme in the institution with representations of teachers, students and university agents, once the theme requires effort of the entire community to achieve the expected results.